Ultrasonic Simulation Research of Two-Dimensional Distribution in Gas-Solid Two-Phase Flow by Backscattering Method - FAN, Jinhui; WANG, Fei (Archives of Acoustics, 2022)
The two-dimensional distribution of gas-solid flow parameters is a great research significance to reflect the actual situation in industry. The commonly used method is the ultrasonic tomography method, in which multiple probes are arranged at various angles, or the measurement device is rotated as that in medicine, but in most industrial situations, it is impossible to install probes at all angles or rotate the measured pipe. The backscattering method, however, uses only one transducer to both transmit and receive signals, and the two-dimensional information is obtained by only rotating the transducer. Ultrasound attenuates greatly in the air, and the attenuation changes with frequency. Therefore, Comsol is used to study the reflection of particles with different radii in the air to ultrasound with various frequencies. It is found that the backscattering equivalent voltage is the largest when the product of ultrasonic frequency and particle radius is about 27.78 Hz·m, and the particle concentration of 30% causes the strongest backscattering. The simulated results are in good agreement with the Faran backscattering model, which can provide references for selecting the appropriate frequency and obtaining the concentration when measuring gas-solid two-phase flow with the ultrasonic backscattering method.